(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study examines the distinctive cognitive characteristics exhibited across different age groups, analyzing the developmental trajectories of mental processes from early childhood through late adulthood. The research explores how cognitive functions including attention, memory, problem-solving abilities, and executive functioning evolve throughout the human lifespan. By investigating both normative developmental patterns and individual differences, this study identifies key cognitive transitions between developmental stages and examines how social, educational, and environmental factors influence cognitive development. The findings provide valuable insights for educational practices, clinical interventions, and supportive strategies tailored to age-specific cognitive needs.